Spain : Financial Sector Assessment Program; Detailed Assessment of Observance of the IAIS Insurance Core Principles. (IMF Staff Country Reports; Country Report ;, 2006)
This paper presents a detailed assessment of the observance of the Insurance Core Principles (ICP) of the International Association of Insurance Supervisors (IAIS) in Spain. The IMF, for their assessment, consulted the review of a self-assessment prepared by the General Directorate of Insurance and Pension Funds (DGSFP), comments from Private Insurance Organization and Supervision Law (LOSSP) and other secondary regulations on the insurance activity, and notes and presentations on several regulatory and supervisory issues. Also, discusses the recommended action plan and authorities' response to the assessment.